Aspects of hydrocarbon potential and clay mineralogy of the patti formation, southern Bida Basin, Nigeria (2013)
"Among the major lithostratigraphic units making up the southern Bida basin are the Lokoja and Patti Formations, overlain by the Agbaja Ironstone. Outcrop samples from the associated shales and claystones units of the Patti formation were examined and characterized to deduce the hydrocarbon potential of the associated shales as well as determine the clay mineralogy in other to deduce the provenance and the palaoclimatic setting of thr basin. Altogether, a total of sixteen samples, made up of ten (10) shale and six (6) claystones were analyzed for this study. Field relationships show that the sediments are cyclical. The shales are dark to greyish while the claystones are milky to whitish. Within the sequences are associated ironstone, sandstones and mudstone. The result of Total Organic Carbon (TOC) ranges from 1.73 to 3.45 wt%, which is greater than 0.5 wt% threshold for clastic rocks to be considered as good source rocks. The Hydrogen Index(HI) ranges from 28 to 79 mgHC/gTOC. This value reveals terrestrial type IV organic matter. Cross plots of Hydrogen Index (HI) versus Oxygen Index (OI), S2 vs TOC indicate types III and type IV organic matter. In addition, cros plot of HI vs Tmax shows immature sediments and mainly type IV organic matter. Tmax values range from 418 to 428oC while the Production Index (PI) ranges from 0.04 to 0.13, which further indicate immature sediments. The clay mineralogy reveals kaolinite as the major clay mineral type, comprisisng 21.28 to 60.48%, dickite (6.00%) whiles the non-clay minerals are mainly quartz, hemalite and feldspar. It can be deduced that the shales are immature with terrestrial organic matter having potential to generate gas at appropriate maturation. The Prevalence of kaolinite is attributable to weathering of feldspar-rich, rocks from the adjoining basement rocks under warm, humid climatic setting. "